Factores asociados a mortalidad intrahospitalaria de una población en hemodiálisis en el Perú - Herrera Añazco, Percy (2015)
Objectives. To determine the factors associated with mortality during the first hospitalization of patients admitted to a hemodialysis unit. Materials and methods. Observational and retrospective study of patients admitted to “Dos de Mayo” National Hospital between January 2012 and December 2013. For the survival analysis we used the Kaplan-Meier method. A multivariate logistic regression was performed to evaluate the factors associated with hospital mortality. Results. 216 patients with a mean age of 56.9 ± 15.5 years were studied. 24% of patients (n = 51) died during their hospital stay. The mortality rate was 9.3 deaths/100 person-weeks (95% CI: 7.0 to 12.3). We found a tendency of less risk of death in patients with between 1 and 6 months from chronic kidney disease diagnosis (OR 0.84, 95% CI: 0.32 to 2.26) and in those with more than six months from chronic kidney disease diagnosis compared with those who had less than a month from chronic kidney disease diagnosis (OR 0.55, 95% CI: 0.19 to 1.57). Previous care by a nephrologist was not associated with differences in lower mortality (OR 1.14, 95% CI: 0.39 to 3.31). Conclusions. There is poor prior care among hemodialysis patients that form part of an inadequate health care structure and this is associated with high inhospital mortality.